In vitro and in vivo regeneration of Oryza sativa L. cv. MR219 and Zea mays L. var. rugosa by apical meristem tissues - Silvarajan, Lavanya (2013)
Conventional propagation of important cereal crops such as corn and rice are vulnerable to unpredictable climatic changes. To ensure the constant availability of these crops, it is important to look towards alternative propagation methods such as in vitro regeneration. To date, there are limited reports of an ideal in vitro regeneration protocol of both rice and corn from shoot apical meristem (SAM) and no reports on root apical meristem (RAM) as explant. Thus, the objective of the present study is to establish an ideal in vitro regeneration system for Malaysian indica rice MR219 and Thai Super Sweet corn. Regeneration was successfully achieved by means of shoot and root apical meristem (SAM and RAM) obtained from 4-day old germinating seedlings through tissue culture. The study found that primary shoot was successfully induced from SAM and RAM of MR219 rice on liquid MS medium supplemented with 0.1 mg L–1 KIN (kinetin) and 0.2 mg L–1 KIN respectively. Vigorous primary shoots were induced from SAM and RAM of Thai Super Sweet corn on liquid MS medium supplemented with 0.15 mg L–1 KIN and only liquid MS medium respectively. Following this, shoot multiplication from SAM of MR219 rice was highest on solid MS medium supplemented with a combination of 1.5 mg L–1 KIN and 0.05 mg L –1 IAA (indole-3-acetic-acid) with an average of 8.8 ± 0.22 shoots. RAM of MR219 rice required solid MS medium supplemented with a combination of 2.0 mg L–1 KIN and 0.05 mg L–1 IAA with an average of 5.7± 0.17 shoots. Shoot multiplication of Thai Super Sweet corn was highest for SAM and RAM on solid MS medium supplemented with a combination of 3.0 mg L–1 KIN and 0.01 mg L–1 IAA and solid MS medium supplemented with a combination of 3.0 mg L–1 KIN and 0.15 mg L–1 IAA with an average of 13.1 ± 0.16 and 6.3 ± 0.19 shoots. In both species,shoot multiplication was in concomitant with root formation for both explants on ideal treatments. Regenerated plantlets survived greenhouse conditions upon acclimatization with a satisfying survival rate of more than 80% and 60% for plantlets produced from SAM and RAM of both species respectively. In conclusion, the highly efficient and economic protocol suggested in this study can be applied as an alternative to conventional propagation method for the large-scale production of MR219 rice and Thai Super Sweet corn throughout the year.